CRIMINOLOGICAL STUDY OF ILLEGAL RACING BY CHILDREN (Study at Medan Police Headquarters) - Muhammad Ody Alwy Siregar; Nursariani Simatupang (Inspiring Law Journal, 2026)
Ilegal racing is a phenomenon that often poses risks and dangers to the community. This practice involves illegal racing on highways, often carried out at high speeds and without regard for traffic regulations. In addition to endangering the lives of drivers and others around them, illegal racing also damages road infrastructure and disrupts public order and security. The phenomenon of illegal racing, as a form of juvenile delinquency, will become a major problem if not addressed quickly and appropriately. Illegal racing is an act prohibited and regulated by positive law in Indonesia. This illegal racing causes fear and concern in the community because the risks faced are very high, ranging from dealing with the police, accidents resulting in disability and even death. The research problem formulation in this study is what is the modus operandi of illegal racing carried out by children in Medan City, what are the factors causing illegal racing carried out by children, and what solutions can be provided to prevent illegal racing carried out by children.The illegal racing methods practiced by children in Medan are essentially similar to those in other regions: groups, nighttime until early morning, and utilizing deserted public roads. However, there are distinct urban characteristics, such as the use of social media to schedule times and locations, the involvement of motorcycle communities or gangs, and the primary goal of seeking thrills. The factors contributing to illegal racing among children are influenced by a combination of internal and external factors. Internally, curiosity, adrenaline, a search for identity, and a desire for peer recognition are the main triggers. Externally, there is a lack of parental supervision and weak social control within the community. The Medan Police's solution to preventing illegal racing among children involves a repressive, preventive, and educational approach.